Análise da intenção de evasão da pós-graduação: um estudo multifatorial em uma IES pública - Malaquias, Gabriela dos Santos (2024)
Dropout from master's and doctoral programs leads to financial, intellectual, and scientific losses for a country. With this justification, the objective of this research was to identify the causes of dropout intention in master's and doctoral programs at a public higher education institution (HEI), as well as to explore students' perceptions regarding graduate education, investigate potential relationships between the studied variables and the causes of dropout intention, assess differences in perceptions among groups of respondents, and provide a technical report on the topic to the HEI. To achieve the proposed objectives, a survey-based research instrument was developed and sent to all students currently enrolled in master's and doctoral programs at the HEI. The quantitative data obtained were analyzed using descriptive and multivariate statistics, including exploratory factor analysis, multiple linear regression, and T-tests and ANOVA. The results identified eight reasons that influence the dropout intention within the sample. The most influential reason was a lack of motivation for conducting research, followed by the quality of education and financial and professional difficulties. Furthermore, the relationship with the advisor, academic burnout, logistical challenges, scholarships, and race/ethnicity also emerged as factors influencing the intention to drop out. The study offers theoretical, practical, and social contributions, including identifying and deepening the understanding of variables that influence dropout intention, providing support for the development of public policies and institutional actions, and highlighting that the dropout issue is not solely the student's responsibility but a shared one. Additionally, a technical report on the dropout topic was developed for the studied HEI, presenting data and proposals to mitigate graduate students' dropout intentions.